The macroeconomics of aid: overview - Addison, Tony; Morrissey, Oliver; Tarp, Finn (Taylor & Francis, 2017)
This Special Issue explores macroeconomic effects of aid from various perspectives through a blend of studies, both conceptual and empirical in nature. The overall aim is to enhance the understanding of the macroeconomic dimensions of aid in the policy and research communities, and to inspire further innovative work in this important area. This opening article provides a scene setting summary of five generations of aid research, with a particular focus on how the JDS has contributed to this literature, and ends with an overview of the papers included in this Issue.